Intracellular ATP Increases Capsaicin-Activated Channel Activity by Interacting with Nucleotide-Binding Domains - Kwak, Jiyeon (J Neurosci, 2000)
Capsaicin (CAP)-activated ion channel plays a key role in generating nociceptive neural signals in sensory neurons. Here we present evidence that intracellular ATP upregulates the activity of capsaicin receptor channel. In inside-out membrane patches isolated from sensory neurons, application of CAP activated a nonselective cation channel (i(cap)). Further addition of ATP to the bath caused a significant increase ini(cap), with aK(1/2) of 3.3 mm. Nonhydrolyzable analogs of ATP, adenylimidodiphosphate and adenosine 5′-O-(3-thio)-triphosphate, also increasedi(cap). Neither Mg(2+)-free medium nor inhibitors of various kinases blocked the increase in i(cap) induced by ATP. The enhancing effect of ATP was also observed in inside-out patches of oocytes expressing vanilloid receptor 1, a cloned capsaicin receptor. Single point mutations (D178N, K735R) within the putative Walker type nucleotide-binding domains abolished the effect of ATP. These results show that ATP increasesi(cap) in sensory neurons by direct interaction with the CAP channel without involvement of phosphorylation.